The Concept of Ta’lim-Based Learning: An Exploration of Increasing Students’ Critical Reasoning - Syahidin, Syahidin; Syafei, Makhmud; Firmansyah, Mokh. Iman (TARBAWY: Indonesian Journal of Islamic Education, 2022)
Abstract Teenagers at this time are easily influenced by hoax news, so that it can lead to incorrect understanding. This indicates that in general teenagers just follow it without thinking critically in understanding the news circulating. With a qualitative approach to the design of the literature study, this study found several essential things. First, the lack of critical thinking in adolescents is due to factors from learning patterns that tend to be rote and this is incomplete in the view of the ta’lim concept. Second, the concept of ta’lim provides flexibility for students to continue to develop their critical thinking skills. Thus, the educational process is not just a transfer of knowledge but more than that, every student is required to use every potential that exists such as the potential to listen, see, and most importantly the potential to think critically.Abstrak Remaja pada saat ini sangat mudah terpengaruh oleh berita hoax, sehingga dapat menimbulkan pemahaman yang tidak benar. Ini  menandakan pada umumnya remaja hanya mengikuti saja tanpa berpikir kritis dalam memahami berita yang beredar. Dengan pendekatan kualitatif desain studi literatur penelitian ini menemukan beberapa hal esensial. Pertama Kurangnya berpikir kritis pada remaja karena faktor dari pola pembelajaran yang cenderung ke hafalan dan ini kurang lengkap jika dalam pandangan konsep ta’lim. Kedua, Konsep ta’lim memberikan keleluasaan pada siswa untuk terus mengembangkan kemampuan berpikir kritisnya. Sehingga, proses pendidikan tidak hanya sekadar transfer ilmu pengetahuan melainkan lebih dari itu, setiap siswa dituntut untuk menggunakan setiap potensi yang ada seperti potensi mendengarkan, melihat, dan yang terpenting potensi berpikir kritis.